High Bioavailability from Ferric Pyrophosphate-Fortified Bouillon Cubes in Meals is Not Increased by Sodium Pyrophosphate: a Stable Iron Isotope Study in Young Nigerian Women. Issue 5 (20th April 2019) - Eilander, Ans; Funke, Olumakaiye M; Moretti, Diego; Zimmermann, Michael B; Owojuyigbe, Temilola O; Blonk, Cor; Murray, Peter; Duchateau, Guus S
ABSTRACT: Background: It is challenging to find an iron compound that combines good bioavailability with minimal sensory changes when added to seasonings or condiments. Ferric pyrophosphate (FePP) is currently used to fortify bouillon cubes, but its bioavailability is generally low. Previously, the addition of a stabilizer, sodium pyrophosphate (NaPP), improved iron bioavailability from a bouillon drink. Objective: We assessed whether there is a dose-response effect of added NaPP on iron bioavailability from local meals prepared with intrinsically labeled FePP-fortified bouillon cubes in young Nigerian women using iron stable isotope techniques. Methods: In a double-blind, randomized, cross-over trial, women ( n  = 24; aged 18–40 y; mean BMI 20.5 kg/m 2 ) consumed a Nigerian breakfast and lunch for 5 d prepared with bouillon cubes containing 2.5 mg 57 Fe (as FePP) and 3 different molar ratios of NaPP: 57 Fe (0:1, 3:1, and 6:1). Iron bioavailability was assessed by measuring 57 Fe incorporation into erythrocytes 16 d after each 5 d NaPP: 57 Fe feeding period. Data were analyzed using a linear regression model of log iron absorption on NaPP ratio, with body weight and baseline body iron stores as covariates and subject as a random intercept. Results: Of the women included, 46% were anemic and 26% were iron deficient. Iron bioavailability was 10.8, 9.8, and 11.0% for the 0:1, 3:1, and 6:1 NaPP: 57 Fe treatments, respectively. There was no dose-response effect of an increasing NaPP: 57 Fe ratio (β ± SE: 0.003 ± 0.028, P  = 0.45). Conclusions: In this study, the addition of NaPP did not increase iron bioavailability from FePP-fortified bouillon cubes. However, iron bioavailability from the Nigerian meals prepared with FePP-fortified bouillon cubes was higher than expected. These results are encouraging for the potential of bouillon cubes as a fortification vehicle. Further studies are needed to assess the effect of FePP-fortified bouillon cubes on improving iron status in low-income populations. This trial was registered at clinicaltrials.gov as NCT02815449.